Meaningful Learning with Digital Module: Innovation in High School Physics Learning on Waves - Fitriani, Wulandari; Asyifa Irchami, Rachma; Bakri, Fauzi (Program Studi Pendidikan Fisika Universitas Negeri Jakarta, LPPM Universitas Negeri Jakarta, HFI Jakarta, HFI, 2025)
The development of 21st-century technology demands innovations in learning media that can support critical, creative, collaborative, and communicative thinking skills. In the context of physics learning, students often still face difficulties in understanding abstract concepts, including Wave material, due to limitations in visualization and the connection between theory and real phenomena. This study aims to develop a digital module based on Meaningful Learning in Wave material as an alternative learning medium that is more interactive, contextual, and aligned with current demands. The research employs the Research and Development (R&D) method using the Dick & Carey model to develop the digital module. Expert validation shows a very good level of feasibility with percentages of 92.5% for the media aspect, 79.2% for the material aspect, and 88.3% for the learning aspect. A limited trial involving 22 students produced positive responses with an average of 92.38%. These results demonstrate that the digital module is not only feasible for use but also effective in helping students connect prior knowledge with new concepts through concept maps, images, animations, and interactive videos. The developed digital module is equipped with concept maps, learning outcomes, illustrations, animations, and interactive videos, which have been proven to help students connect prior knowledge with new concepts, thereby supporting the achievement of meaningful learning. Thus, the digital module based on Meaningful Learning in Wave material can serve as an innovative alternative learning medium to enhance students’ conceptual understanding and 21st-century skills.